Pengembangan Pengembangan Media Pembelajaran Seni Musik Berbasis PowerPoint (PPT) Interaktif Materi Not Balok pada Siswa SMP - Ananda Faiqoh; Trisakti . (Jurnal Pendidikan Sendratasik, 2026)
This study, conducted at SMP Negeri 14 Gresik, was motivated by students’ low understanding of and motivation toward staff notation due to the continued use of conventional teaching methods. Initial survey results showed that 67% of students had not yet fully understood staff notation. Therefore, engaging and interactive learning media are needed. This study aims to describe the development process, quality, and effectiveness of interactive PowerPoint (PPT)-based learning media for staff notation. The method used was Research and Development (R&D) based on the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of eighth-grade students and Cultural Arts teachers. Validation was conducted by subject matter experts and media experts to assess the suitability of the media. The results showed that the media was developed systematically in accordance with the ADDIE stages. The quality of the media received scores of 90.6% from subject matter experts and 87.5% from media experts, both categorized as highly suitable. The effectiveness of the media was demonstrated by student responses of 92.8%, categorized as highly effective. Thus, the interactive PPT-based learning media on staff notation is considered suitable and effective for use in junior high school music education.